Obecność Adama Mickiewicza w dziełach Julii Hartwig = In the constellation of Romantic forms and genres. The poetry of Julia Hartwig - Kulczycka, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author of the article demonstrates that Julia Hartwig`s poetic imagination was strongly anchored in world Romantic literature and culture, particularly French and Polish. Letters, diaries, flashes - were her favourite forms. The latter may be compared to extended Norwid`s parables of "white" and "black" flowers or to Mickiewicz`s concise "sentences and remarks", even if the author of Błyski (Flashes) shied away from pure aphorism and sententiousness.
Keywords: Mickiewicz, Adam (1798-1855); Hartwig, Julia (1921-2017); błyski; parabole; zdania i uwagi; flashes; parables; sentences and remarks